Financial constraints and international trade with endogenous mode of competition - Bouët, Antoine; Vaubourg, Anne-Gaël (Journal of Banking & Finance, 2016)
The paper examines how financial constraints affect firms’ decisions to export when the mode of intra-sectoral competition is endogenous. We propose an extension of Neary and Tharakan’s (2012) model, in which firms resort to external funders to finance investments in production capacities. Sectors differ in financial constraint and the cost of capital increases with the level of financial constraint. We first show that a weaker financial constraint allows firms to adopt a Cournot (rather than a Bertrand) pricing scheme and generate a high duopoly profit. Consequently, less financially constrained sectors are more likely to export. We also exhibit a new transmission channel of financial crisis. By increasing the financial cost of exporting and making it more difficult to engage in a Cournot behavior, a financial shock reduces both the intensive and extensive margins of trade.